2016
DOI: 10.1371/journal.pone.0151085
|View full text |Cite
|
Sign up to set email alerts
|

Activity Based High-Throughput Screening for Novel O-GlcNAc Transferase Substrates Using a Dynamic Peptide Microarray

Abstract: O-GlcNAcylation is a reversible and dynamic protein post-translational modification in mammalian cells. The O-GlcNAc cycle is catalyzed by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). O-GlcNAcylation plays important role in many vital cellular events including transcription, cell cycle regulation, stress response and protein degradation, and altered O-GlcNAcylation has long been implicated in cancer, diabetes and neurodegenerative diseases. Recently, numerous approaches have been developed to identify OGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…To fast track the identification of OGT substrates, peptide microarrays have been developed, whereby thousands of proteins can be screened simultaneously for their ability to be OGT substrates [120,121]. To fast track the identification of OGT substrates, peptide microarrays have been developed, whereby thousands of proteins can be screened simultaneously for their ability to be OGT substrates [120,121].…”
Section: Prediction Of Phosphorylation/ O-glcnacylation Crosstalkmentioning
confidence: 99%
“…To fast track the identification of OGT substrates, peptide microarrays have been developed, whereby thousands of proteins can be screened simultaneously for their ability to be OGT substrates [120,121]. To fast track the identification of OGT substrates, peptide microarrays have been developed, whereby thousands of proteins can be screened simultaneously for their ability to be OGT substrates [120,121].…”
Section: Prediction Of Phosphorylation/ O-glcnacylation Crosstalkmentioning
confidence: 99%
“…3.2.4. Peptide microarray‐based OGT assay : Recently, a peptide microarray‐based OGT assay (Figure ) was derived from a protein microarray OGT assay approach, which was originally designed to identify protein substrates for OGT isoforms by using an array of commercially available proteins bound to a chip. In this assay, proteins or peptides are subjected to OGT‐catalyzed glycosyl transfer, followed by fluorescent antibody detection of O‐GlcNAcylation.…”
Section: O‐glcnac Transferase (Ogt)mentioning
confidence: 99%
“…In this method, a highly purified form of OGT is not necessary, and the kinetic activity of the enzyme can be measured by scanning the signal at regular intervals. Utilizing this peptide microarray‐based assay, retinoblastoma‐like 2 protein (RBL‐2), which is a key regulator of entry into cell division and proposed to be a tumor suppressor, was identified as an OGT substrate, and its O‐GlcNAc modification site (Ser420) was recapitulated . However, the sensitivity of this method depends on the anti‐O‐GlcNAc antibody used in this assay, which has relatively low detection sensitivity.…”
Section: O‐glcnac Transferase (Ogt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide microarrays were later used to examine the substrate specificity of different OGT isoforms. Using RL2 (an anti‐ O ‐GlcNAc antibody) for O ‐GlcNAc detection, one study found that a number of peptides were glycosylated at different levels by each of the three OGT isoforms, thus indicating differential substrate specificities . Besides applications in studying OGT, a microarray with synthetic glycopeptides was also developed for OGA, which could be used in the future to investigate the substrate preferences of this hydrolase.…”
Section: Introductionmentioning
confidence: 99%